(untitled) (Educação e Pesquisa, 2009)
Brazili's school system has a high above-age rate, that is, a high percentage (over 60%) of students whose age is above the school age expected for the school year they are enrolled in. In this article we look into the mechanisms responsible for above-age from a sociological perspetive, and inquire whether its causes are found both in the way social actions are structured and in the norms that make up the social structure. Our hypothesis is that the major cause for above-age is found in the cultural gap between the school system and the students' disadvantaged social and financial backgroung, especially those with African descent. However, another cause observed derives from individual dicisions. Certainly, individuals with this social bacground decide to take up again the subjects they have not yet passed, but their academic results and their expectations for the future suffer from the dificulties awaiting along their schooling. Class and ethnic slant seem to aggravate due to students' differing perceptions on the advantages and disadvantages in continuing with their studies. Our analysis, therefore, shows these circumstances considering social actions and structural conditions (cf. el modelo de Boudon, 1983; Goldthorpe, 1996).